The Influence of Earnings Per Share and Return On Investment on Stock Prices in The Banking Sector Listed on IDX - Budhiarjo, Intan Sari; Dewi, Iriana Kusuma (Yayasan Pendidikan Penelitian Pengabdian Al-amsi, 2025)
This study aims to examine the effect of Earnings Per Share (EPS) and Return on Investment (ROI) on stock prices in the banking sector listed on the Indonesia Stock Exchange. A quantitative approach is employed using secondary data from published financial statements. The sample consists of six banking companies selected from a population of 46 firms based on predetermined criteria. Data analysis includes descriptive statistics, panel data regression, hypothesis testing, and the coefficient of determination. The results show that EPS does not have a significant partial effect on stock prices, while ROI has a significant positive effect. Simultaneously, EPS and ROI significantly influence stock prices, indicating that profitability indicators play an important role in explaining stock price movements in the Indonesian banking sector.